Managing Game-Related Conflict With Parents of Young Adults With Internet Gaming Disorder: Development and Feasibility Study of a Virtual Reality App - Shin, Yu-Bin; Kim, Jae-Jin; Kim, Hyunji; Kim, Soo-Jeong; Eom, Hyojung; Jung, Young Hoon; Kim, Eunjoo (JMIR Publications, 2021)
BackgroundIndividuals with internet gaming disorder (IGD) report facing family conflicts repeatedly because of their excessive internet gaming. With recent advancements in virtual reality (VR) technology, VR therapy has emerged as a promising method for the management of various psychiatric disorders, including IGD. Given that several risk and protective factors for young people with addiction can be influenced by their interpersonal context, the potential utility of VR-based apps for managing family conflicts needs to be examined with reference to IGD management. However, few studies have evaluated potential treatment modules related to interpersonal conflict management, such as emotion regulation and taking the perspective of others. ObjectiveThis preliminary study aims to examine the potential use of a VR-based app in the management of game-related conflicts with parents of young adults with IGD and matched controls. MethodsIn total, 50 young male adults (24 with IGD and 26 controls) were recruited to participate in the study. We developed a virtual room where game-related family conflicts arise. Using this room, participants completed 2 VR tasks that required them to express anger and then implement coping skills (ie, risk/benefit assessment of stopping a game and taking parents' perspective) to deal with negative emotions in interpersonal conflict situations and to decrease one's gaming behavior. ResultsThe results showed that immersion in our VR app tended to provoke negative emotions in individuals with IGD. In addition, after a risk/benefit assessment of stopping a game, the response of stopping a game immediately increased significantly in the IGD group, suggesting that patients' gaming behavior could be changed using our VR program. Furthermore, in individuals with IGD, longer gaming hours were associated with a lower level of perceived usefulness of the coping skills training. ConclusionsThe findings of this study indicate that our VR app may be useful for implementing more desirable behaviors and managing gaming-related family conflicts in individuals with IGD. Our VR app may offer an alternative for individuals with IGD to learn how a vicious cycle of conflicts is developed and to easily and safely assess their dysfunctional thoughts behind the conflicts (ie, perceived unreasonable risks of stopping a game and thoughts acting as a barrier to taking the perspective of others).